ANALISIS HUBUNGAN TINGKAT PENDIDIKAN DENGAN PERILAKU KONSUMSI RUMAH TANGGA MASYARAKAT INDONESIA - Nauval Haiban Ginting (Bajang Institute, 2022)
This study aims to examine the analysis of the relationship between education level and household consumption behavior of Indonesian people. As in general, the first education a child gets is through the family. And the level of life is said to be peaceful when the family is able to meet the needs of life, both physically and spiritually. Just like spending costs for consumption, we must also pay attention to what the costs are spent on. Then the level of education of the child can be seen from the consumption. The sample of this research is the Indonesian people with a database in 2020. In this study, the research method used in this research is using a library research system.